ISR as Proction of CSR Disclosure Bank Muamalat Indonesia and Bank Syariah Mandiri - Irman Firmansyah (Jurnal Ilmiah ESAI, 2014)
This research aims to detect Islamic social disclosure in Islamic bank in Indonesia that measuresed with Islamic Social Reporting (ISR) Index. This research is done in two biggest Islamic banks in Indonesia that are Bank Muamalat Indonesia and Bank Syariah Mandiri for look comparison Islamic social disclosure. Analyzer applied in this research is content analysis. The result shows that Islamic social disclosure in Bank Syariah Mandiri is higger than Bank Muamalat Indonesia. But either Bank Muamalat Indonesia or Bank Syariah Mandiri not yet show result perfect disclosure measuresed from Islamic social reporting.Keywords: Islamic Social Reporting, bank muamalat Indonesia, bank syariah mandiri